Interpretasi Konsep Tuhan Perspektif Maulana Makhdum Ibrahim dalam Kitab Primbon Bonang dan Suluk Wujil - Jauharotina Alfadhilah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
This article analyzes the concept of God according to Sunan Bonang's view in his works, namely Primbon Bonang and Suluk Wujil. This article concludes that the two books are a compendium of Sunan Bonang's Sufism and his spiritual journey during his life. Sunan Bonang explains that the first step that must be done by the sÄlik before embarking on a spiritual journey is trying to know himself and multiply wirid and zikir. Sunan Bonang's type of sufism can be categorized Sunnī Sufism, which rejects the concept of Waḥdat al-Wujūd. Alternatively, he proposes a new concept called